2018
DOI: 10.1159/000493966
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Genetic Mutations in Papillary Thyroid Cancer Detected by Whole Exome Sequencing

Abstract: Background/Aims: The purpose of the study was to investigate the altered driver genes and signal pathways during progression of papillary thyroid cancer (PTC) via next-generation sequencing technology. Methods: The DNA samples for whole exome sequencing (WES) analyses were extracted from 11 PTC tissues and adjacent normal tissues samples. Direct Sanger sequencing was applied to validate the identified mutations. Results: Among the 11 pairs of tissues specimens, 299 single nucleotide variants (SNVs) in 75 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The driver gene list includes the genes in the COSMIC cancer gene census (v.87), genes identified in TCGA with q < 0.05 and previous large-scale studies. 36,[47][48][49][50][51] Any variant present in these genes underwent classification based on the following criteria. If the gene was classified as tumor suppressor by COSMIC and the variant was found to be deleterious (stop-gain or predicted deleterious in two of the three computational tools-Sift, PolyPhen, and MutationTaster), the specific variant was classified as a driver.…”
Section: Driver Mutation Classificationmentioning
confidence: 99%
“…The driver gene list includes the genes in the COSMIC cancer gene census (v.87), genes identified in TCGA with q < 0.05 and previous large-scale studies. 36,[47][48][49][50][51] Any variant present in these genes underwent classification based on the following criteria. If the gene was classified as tumor suppressor by COSMIC and the variant was found to be deleterious (stop-gain or predicted deleterious in two of the three computational tools-Sift, PolyPhen, and MutationTaster), the specific variant was classified as a driver.…”
Section: Driver Mutation Classificationmentioning
confidence: 99%
“…[ 22 , 23 ] Fang et al . [ 6 ] reported that T:A>C:G was observed in nearly one-half of their subjects with papillary thyroid cancer (PTC), whereas the C>T/G>A substitution was the most common pattern in somatic mutations as shown by WES results for PTC. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…WES is one of the NGS platforms that can detect variations in the protein-coding area of genes (exons), which account for approximately 3.09% of the whole genome (12). Its function and application to detect disease-causing mutations have been previously demonstrated in papillary thyroid cancer cases (13)(14)(15)(16) and other clinical studies (17,18).…”
Section: Discussionmentioning
confidence: 99%